The effect of food and service quality towards consumer purchase intention: a case study in fast food restaurant Malaysia / Zatul Iffah Mohd Fuza ... [et al.] - Mohd Fuza, Zatul Iffah; Md Sharif, Mohd Shazali; Akbarruddin, Mohd Noor Azmin; Mazlan, Nursyamimi; Badarudin, Nur Nabilah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
Recognizing the importance of quality management, particularly in terms of food and service quality, is crucial for businesses to thrive in the contemporary competitive landscape. Quantitative approach was used, to collect data from a sample of 385 fast-food consumers in Malaysia via Google Forms. Questionnaire was designed to evaluate not only perceptions of food and service quality and their influence on purchase intentions but also to gather detailed demographic information and consumption patterns of the respondents. This study revealed a positive correlation between both food quality and service quality and consumer purchase intentions. This indicates that efficient service and high-quality food offerings can significantly increase purchase intent in fast-food restaurants. Hence, this study underscores the significance of quality management within the fast-food industry and provides valuable insights for businesses aiming to enhance customer loyalty and purchase intention.